Developing suicide screening and prevention guideline for the children and adolescents of Pakistan: The first step - Ahsan Nazeer (17112876) (2025)
This paper focuses on developing suicide screening and prevention guidelines by the Pakistan Psychiatric Research Center’s Task Force of national and international experts, specifically for children and adolescents in Pakistan. The discussion included screening for youth in medical and non-medical settings using internationally recognized, validated, and easy-to-use screening instruments. Recommendations were also made to advance beyond the current paradigm in Pakistan's mental health landscape by exploring essential next steps to reduce youth suicide rates by 2030. Pakistan has an estimated population of 240 million, with 41 % under the age of 15. It is believed that around 35 % of Pakistani youth experience emotional difficulties, with stress, anxiety, and depression being the most pressing concerns within this group. Key factors contributing to these challenges include academic pressure, intensified by societal and parental expectations, excessive social media use, as well as family dynamics, which encompass strict parenting, and a perceived lack of emotional support. Existing studies have identified an increased risk of suicide among Pakistani adolescents aged 15–18, with the ingestion of poisonous substances as the most common method, followed by hanging, jumping in front of trains, and firearm use. Systemic barriers, including limited financial resources, a shortage of trained mental health professionals, and societal stigma, impede progress. Nevertheless, ample opportunities for improvement exist. Raising public awareness to combat stigma, promoting inter-sectoral collaboration, and enhancing policy implementation are essential steps. A multi-stakeholder approach that includes policymakers, educators, families, and young people is crucial for building a sustainable mental health ecosystem. Other Information Published in: Asian Journal of Psychiatry License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ajp.2025.104586